Pengaruh Waktu Milling Terhadap Sifat Desorpsi Material Penyimpan Hidrogen MgH2-Ni Melalui Teknik Mechanical Alloying - Nirmala Sari; T. Andi Fadlly; Maulinda Maulinda (Jurnal Serambi Engineering, 2021)
Hydrogen is a renewable energy source that can be used as a fuel and as an  alternative to fossil fuels. Solid  storage media in solid form are safer to use than liquid (-253 oC) or gaseous media (700 bar) media. To store hydrogen in a solid medium, it requires a metal able to  interact with hydrogen . Magnesium is one of the metals which  can form metal hybrids based on MgH2 which is capable of  absorbing hydrogen up to  (7.6wt%). However, the reaction kinetics for  magnesium are  very slow, it takes at least 60 minutes to absorb hydrogen and the operating temperature is always  very high (300 oC). Several attempts have been made to add the catalytic converter  and milling time. Hydrogen storage material based on MgH2 with a 10wt%Ni catalyst was  successfully synthesized using a mechanical alloy technique with time variations of 2 hours, 5 hours, and 10 hours. From the results of the X-ray diffraction schema  at a diffraction angle of 2θ=37.87o, it shows the presence of a MgH2 phase, Ni phase is at a diffraction angle of 61.85o, the diffraction peak also shows that there was a  widening of the diffraction peak with increasing milling time, this explains that there was  a reduction in the size of the crystal. When  calculating  with the Schereer method, the crystal size of the material reaches 10 nm. The results of the DSC test indicated  a decrease in temperature of 383 oC in 41 minutes with a milling time of 10 hours.